Responsiveness to immune checkpoint inhibitors versus other systemic therapies in RET-aberrant malignancies. Issue 5 (23rd October 2020) - Hegde, Aparna; Andreev-Drakhlin, Alexander Y; Roszik, Jason; Huang, Le; Liu, Shuang; Hess, Kenneth; Cabanillas, Maria; Hu, Mimi I; Busaidy, Naifa L; Sherman, Steven I; Dadu, Ramona; Grubbs, Elizabeth G; et al.
Abstract : Purpose: The receptor tyrosine kinase rearranged during transfection (RET) can be oncogenically activated by gene fusions or point mutations. Multikinase inhibitors such as cabozantinib, lenvatinib and vandetanib have demonstrated activity in RET-dependent malignancies, and selective RET inhibitors (Selpercatinib and Pralsetinib) are in clinical trials. However, the responsiveness of RET-dependent malignancies to immune checkpoint inhibitors (ICIs) is unknown. We compared the time to treatment discontinuation (TTD) for ICI versus non-ICI therapy in patients with malignancies harbouring activating RET mutations or fusions (RET+). Methods: A retrospective review of all RET+ patients who were referred to the phase I clinical trials programme at the University of Texas MD Anderson Cancer Center was conducted. TTD was estimated using Kaplan-Meier analysis. Multivariate analysis using the Cox proportional hazard model was performed to identify independent risk factors of treatment discontinuation. Results: Of 70 patients who received systemic therapy for RET+ malignancies, 20 (28.6%) received ICI and 50 (71.4%) received non-ICI therapy. Non-ICI therapy was associated with decreased risk for treatment discontinuation compared with ICI in the overall population (HR=0.31; 95% CI 0.16–0.62; p=0.000834) and in patients with RET point mutations (HR=0.13; 95% CI 0.04–0.45; p=0.00134). In patients with RET fusions, non-ICI therapy was associated with a non-statistically significant decreased risk of treatment discontinuation (HR=0.59; 95% CI 0.25–1.4; p=0.24). ICI therapy and a diagnosis other than medullary thyroid cancer (MTC) were independent risk factors for treatment discontinuation. Conclusion: Our study supports the prioritisation of non-ICI over ICI therapy in patients with RET+ tumours.